Sign In
Ask Question
Amir Glenn
Mathematics
23 September, 21:13
W = 2 Z = 3 (W * Z) + W =
+4
Answers (
2
)
Yuliana Dougherty
23 September, 21:20
0
8
Step-by-step explanation:
W = 2
Z = 3
(W * Z) + W = (2 * 3) + 2
(2 * 3) + 2
6 + 2
= 8
Comment
Complaint
Link
Leslie James
23 September, 21:37
0
8
Step-by-step explanation:
w = 2
z = 3
(w*z) + w = (2*3) + 2
= 6 + 2
= 8
Comment
Complaint
Link
Know the Answer?
Answer
Not Sure About the Answer?
Find an answer to your question 👍
“W = 2 Z = 3 (W * Z) + W = ...”
in 📗 Mathematics if the answers seem to be not correct or there’s no answer. Try a smart search to find answers to similar questions.
Search for Other Answers
You Might be Interested in
Is 3 over 2 the same as 3 over 4?
Answers (1)
What is the answer to 9d-11=6d-5
Answers (2)
Budget $ 150 at $ 8 each plus $10 for delivery how many pizzas van you buy
Answers (1)
Which expressions are equivalent to the one below? 21x/7x
Answers (1)
If a plane is going 110 mph how can it go for 21/2 hours
Answers (2)
New Questions in Mathematics
Combine like terms to create an equivalent expression - 4/7p + (-2/7p) + 1/7
Answers (1)
Alice, ben and carol shared a sum of monet they received, how much money did ben receive
Answers (1)
What is thirty-four and twelve hundredths as a decimal number?
Answers (2)
How many times smaller is 6 is than 60
Answers (2)
Sarah is making strings of beads in the first string she uses 3 beads and she triples the number of beads in each of the next strings identify the number of beads she uses in 5 string
Answers (2)
Home
»
Mathematics
» W = 2 Z = 3 (W * Z) + W =
Sign In
Sign Up
Forgot Password?